Disparities in Completion of Substance Abuse Treatment between and within Racial and Ethnic Groups - Guerrero, Erick G (Blackwell Science Inc, 2013)
OBJECTIVE: To evaluate disparities in substance abuse treatment completion between and within racial and ethnic groups in publicly funded treatment in Los Angeles County, California. DATA SOURCE: The Los Angeles County Participant Reporting System with multicross-sectional annual data (2006–2009) for adult participants (n = 16,637) who received treatment from publicly funded programs (n = 276) for the first time. STUDY DESIGN: Retrospective analyses of county discharge and admission data. Hierarchical linear regressions models were used to test the hypotheses. DATA COLLECTION: Client data were collected during personal interviews at admission and discharge for most participants. PRINCIPAL FINDINGS: African Americans and Latinos reported lower odds of completing treatment compared with Whites. Within-group analysis revealed significant heterogeneity within racial and ethnic groups, highlighting primary drug problem, days of drug use before admission, and homelessness as significant factors affecting treatment completion. Service factors, such as referral by the criminal justice system, enabled completion among Latinos and Whites only. CONCLUSIONS: These findings have implications for reducing health disparities among members of racial and ethnic minorities by identifying individual and service factors associated with treatment adherence, particularly for first-time clients.